Bryozoa from Jørgen Brønlund Fjord, North Greenland. - Andersen, Max (Meddelelser om Grønland, 1973)
From Jørgen Brønlund Fjord, North Greenland, 26 species of Bryozoans are listed. Five species are new to Greenland, viz. Crisia klugei RYLAND, Ramphonotus gorbunovi KLUGE, Tegella armiferoides KLUGE, Escharoides bidenkapi (KLUGE), Escharella octodentata KLUGE.